Ecological and physical factors affecting growth, productivity and herbivory load in the physic nut (Jatropha curcas L.) - Lama, Ang Dawa (fi=Turun yliopisto|en=University of Turku|, 2017)
Jatropha curcas (L.) is a multipurpose oil bearing shrub assumed to be able to survive in a wide range of ecological conditions across the tropical regions of the world. The thesis is composed of two parts, the first one based on experimental research, and the second one on literature reviews. In the experimental part, I assessed the effects of simulated herbivory and drought stress on defence, physiology and compensatory growth of J. curcas seedlings (I and II). In the latter part I reviewed arthropod herbivores, seed yield and genetic variability of J. curcas across the globe (III and IV). Experimental results showed that the highest concentration of flavonoids was found in the leaves of J. curcas seedlings exposed to 50 % herbivory stress and grown in 200 mm y-1 rainfall, whereas the lowest growth and biomass was produced by J. curcas seedlings exposed to 25 % herbivory stress and grown in 200 mm y-1 rainfall (I and II). J. curcas seedlings exhibited an undercompensatory growth response to herbivory stress in all the drought stress levels (II). Our literature review showed that arthropod herbivore load associated with J. curcas was relatively low (78 species) across the globe. Flower and fruit feeders were more common than foliage feeders (III). The highest average genetic diversity was observed, as expected, within the native range of J. curcas (IV) with record levels observed in populations sampled in the State of Chiapas of Mexico. The annual seed yield varied greatly across the globe from 26 to 11,150 kg ha-1; the global mean annual seed yield was 2,220 kg ha-1. Age had a linear whereas rainfall and plant density had a significant quadratic effect on seed yield. Differences in seed yields of J. curcas across the globe might be due to differences in site-specific agro-climatic, soil fertility and genetic factors as well as agronomic practices applied to achieve a high seed yield (IV). Further genetic improvements will be required to produce cultivars which can provide consistently high seed and oil yields. My results contribute to promote commercial production of J. curcas by providing more information on the ecological requirements of the species.

Jatropha curcas (L.) on monikäyttöinen öljykasvi, joka menestyy hyvin vaihtelevissa ekologisissa olosuhteissa maapallon trooppisilla alueilla. Väitöskirjani koostuu kahdesta osasta, kokeellisesta ja kirjallisuuteen perustuvasta. Kokeellisessa osassa tutkin simuloidun herbivorian ja kuivuus käsittelyjen vaikutusta Jatropha curcaksen siementaimien fysiologiaan, puolustukseen ja kompensaatiokasvuun (I ja II). Työni jälkimmäisessä osassa tarkastelen kirjallisuuteen perustuen lajilla tavattavia niveljalkaisherbivoreja sekä siemensadon ja geneettisen monimuotoisuuden vaihtelua levinneisyysalueen eri osissa (III ja IV). Kokeissa havaittiin korkeimmat flavonoidipitoisuudet niiden kasvien lehdissä, joiden lehtipinta-alasta oli poistettu 50 % ja joiden saama sademäärä oli 200 mm v-1, kun taas kasvu oli hitainta ja biomassa pienin niillä kasveilla, joiden lehtipinta-alasta oli poistettu 25 % ja joiden saama sademäärä oli 200 mm v-1 (I ja II). Jatropha curcaksen kasvuvaste herbivoriaan oli alikompensoiva kaikissa kuivuus käsittelyissä (II). Kirjallisuuskatsaus osoitti niveljalkais herbivorian olevan melko vähäistä (kokonaislajimäärä 78 lajia) levinneisyysalueen eri osissa. Kukkien ja hedelmien syöjät olivat lehtibiomassan syöjiä yleisempiä (III). Odotusten mukaisesti geneettinen monimuotoisuus oli suurin lajin alkuperäis alueilla (IV); korkein monimuotoisuus aste havaittiin Meksikossa Chiapasin osavaltion populaatioissa. Vuotuinen siemensato vaihteli levinneisyysalueen eri osissa suuresti välillä 26-11,150 kg ha-1 keskisadon ollessa 2,220 kg ha-1. Kasvin ikä vaikutti satoon lineaarisesti mutta sademäärä ja kasvitiheys kvadraattisesti. Jatrophan siemensadon vaihtelu eri alueiden välillä voi johtua paikallisista ilmasto- ja maaperä olosuhteista, geneettisistä tekijöistä tai sadon lisäykseen käytetyistä viljely tekniikoista (IV). Siemen- ja öljysadon lisääminen vaatii geneettisesti parempien lajikkeiden käyttöönottoa. Työni tulokset hyödyttävät Jatrophan viljely hankkeita tuottamalla tarvittavaa tietoa lajin ekologisista kasvupaikka vaatimuksista.